Permanence and Stability of an Age-Structured Prey-Predator System with Delays - Liming Cai; Xuezhi Li; Xinyu Song; Jingyuan Yu (Discrete Dynamics in Nature and Society)
An age-structured prey-predator model with delays is proposed and analyzed. Mathematical analyses of the model equations with regard to boundedness of solutions, permanence, and stability are analyzed. By using the persistence theory for infinite-dimensional systems, the sufficient conditions for the permanence of the system are obtained. By constructing suitable Lyapunov functions and using an iterative technique, sufficient conditions are also obtained for the global asymptotic stability of the positive equilibrium of the model.